MODERN PROBLEMS OF THE INFLUENCE OF SCIENTIFIC AND TECHNOLOGICAL PROGRESS ON EMPLOYMENT - David Powell (Модернизация, инновация, развитие, 2015)
This article addresses concerns about the impact of technological development on employment. Over recent centuries, innovation has been a driver of technological development and automation, giving rise to fears of an economic disaster where machines increasingly replace workers and there is high unemployment. Despite claims that the idea of permanently high unemployment caused by technological development, "technological unemployment", is discredited, there is good reason to believe that recent trends make Luddite concerns today more valid.